Development and Study of Wound Healing Activity of an Ayurvedic Formulation: Essential Oil of Rosa damascena - Akansha Jain; Shubham Jain; Aakash S. Panwar; Ankit Jainb; Praveen Sharma; G. N. Darwhekar (Iranian Journal of Pharmaceutical Sciences, 2011)
The effect of prepared Ayurvedic formulation was evaluated on excision and incision wound models in rats. The wound-healing activity was assessed by the rate of period of epithelialization and skin-breaking strength. Histological study of the granulation tissue was carried out to know the extent of collagen formation in the wound tissue. The Ayurvedic formulation prepared was then promoted for woundhealing activity in two wound models. The treated animals showed a significant reduction in the wound area and faster rate of epithialisation. In an incision wound model, formulation treated animals demonstrated a significant skin-breaking strength. Histological studies of the tissue obtained from the formulation treated group revealed that the activity was more significant in this group. Our present study reveals that the Ayurvedic formulation posses a potent wound healing activity, which could be a good choice of remedy for wound healing but less potent than standard nitrofurazone.